Sistem Pendukung Keputusan Untuk Kenaikan Jabatan Aparatur Sipil Negara Struktural Dengan Metode SAW - Mya Riska Fitriyani; Didik Kurniawan (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2016)
Local Government Finance and Regional Asset Lampung Tengah Regency is a government agency that is engaged in the field of financial management and regional assets. Employees are resources that very important to determining the success of a work unit. Efforts to improve the quality of the performance of a public servant namely the position increase. Incumbency is the position that indicates the level of a Civil Servants. Incumbency increase is an award given on work performance and dedication Civil Servants. Decision Support System which can help facilitate determining an employee can be said to be worthy for incumbency increase. In this study the calculation method of decision making used is Simple Additive Weighting (SAW) with 6 criteria echelon, working lives of civil servent, working lives of echelon, working lives of incumbency, last education and training. The system is built using the PHP programming language. The test results using Black Box Testing and questionnaires show that the system can be function according to user needs and system is deemed to have the criteria of incumbency increase structural of the Civil Servant in Local Government Finance and Regional Asset Lampung Tengah Regency